2007
DOI: 10.1016/j.vaccine.2007.08.042
|View full text |Cite
|
Sign up to set email alerts
|

Safety and immunogenicity of a high dosage trivalent influenza vaccine among elderly subjects

Abstract: To improve immune responses to influenza vaccine, a trivalent inactivated vaccine containing 60 µg of the HA of each component (A/H3N2, A/H1N1, B) was compared to a licensed vaccine containing 15 µg of the HA of each. More local and systemic reactions were reported by subjects given the high dosage but only local pain and myalgias were significantly increased. The high dosage vaccine induced a higher frequency of serum antibody increases (≥4 fold) in both hemagglutination-inhibiting (HAI) and neutralization te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
94
3
10

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(113 citation statements)
references
References 21 publications
6
94
3
10
Order By: Relevance
“…Inactivated, split trivalent Prospective, randomized, double-blind study with high dose Injection site pain, influenza vaccine and standard dose vaccine, n = 414; 212 M, 202 F, F > M. Couch et al 56 Age range 65-95 yrs. 59 …”
Section: Inactivated Subunit Trivalentmentioning
confidence: 99%
“…Inactivated, split trivalent Prospective, randomized, double-blind study with high dose Injection site pain, influenza vaccine and standard dose vaccine, n = 414; 212 M, 202 F, F > M. Couch et al 56 Age range 65-95 yrs. 59 …”
Section: Inactivated Subunit Trivalentmentioning
confidence: 99%
“…Strategies to optimize responses to vaccination in older adults include the use of adjuvants, 8,36 higher antigen doses, 11,12 ID delivery, 14,25,33,34,37 and addition of a second B strain (quadrivalent influenza vaccine, QIV). Here we report the findings of a study which compared the immunogenicity and safety profiles of low-dose non-adjuvanted ID TIV (containing either 6 µg or 12 µg of A/H3N2 antigen), full-dose non-adjuvanted IM TIV, and full-dose MF59-adjuvanted IM TIV (both IM groups containing either 15 µg or 30 µg of A/H3N2 antigen).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, while MF59 adjuvantation increased pain at the site of injection, and intradermal delivery increased unsolicited adverse events, erythema, induration, and swelling at the injection site, both strategies of vaccination strongly enhanced the immunogenicity of seasonal influenza vaccine in older adults compared with conventional non-adjuvanted intramuscular delivery. adjuvanted trivalent influenza vaccines (aTIVs), [8][9][10] increasing the dose of antigens, [11][12][13] , intradermal (ID) vaccine delivery, 14,15 and virosomal subunit vaccines. 16 …”
Section: Introductionmentioning
confidence: 99%
“…24 The authors also reported no difference in adverse reactions between the regular-dose and high-dose groups, 24 although others have reported that the high-dose vaccine is associated with increased local pain and myalgia. 25 The second novel method of delivering the influenza vaccine is the 2-shot influenza vaccine. Lo et al found that the vaccine response rate of patients who received 2 doses (71%) was significantly higher than that of patients who received one dose (42%; p D 0.006).…”
Section: Inactivated Vaccinesmentioning
confidence: 99%